2020
DOI: 10.3389/fnins.2020.00351
|View full text |Cite
|
Sign up to set email alerts
|

Modulation on Glutamic Pathway of Frontal-Striatum-Thalamus by rs11146020 and rs3813296 Gene Polymorphism in First-Episode Negative Schizophrenia

Abstract: Objectives: The frontal-striatum-thalamus pathway is important in the glutamic neural circuit. The hypofunction of GRIN1 and GRIA2 subunits from glutamic receptors has been hypothesized as the primary process in the etiology of schizophrenia. Identified gene polymorphism involved in the pathogenesis of schizophrenia may uncover relevant mechanism pathways. Methods: We selected two loci of rs11146020 and rs3813296 distributed in GRIN1 and GRIA2 genes and tested their main and interaction effects on causality co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The results show that structural and functional connectivity of the limbic system has changed, including hippocampus, amygdala, etc. [34], as well as insula [35] and thalamus [36], and may consist of part of the mechanism. Changes in these regions based on MRI multi-parameter models are proposed to predict its efficacy [37].…”
Section: Predicting Treatment Responsementioning
confidence: 99%
“…The results show that structural and functional connectivity of the limbic system has changed, including hippocampus, amygdala, etc. [34], as well as insula [35] and thalamus [36], and may consist of part of the mechanism. Changes in these regions based on MRI multi-parameter models are proposed to predict its efficacy [37].…”
Section: Predicting Treatment Responsementioning
confidence: 99%
“…Similar to the effect of KIAA0319 SNPs (rs2038136,rs2038137) genotype, the influence of SNP rs4504469 located at the exon of KIAA0319 coding region on the left Broca upper/lower parietal network and bilateral Wernicke-frontalparietal network is reflected only in controls (Jamadar et al, 2013 ). In addition to investigating the influences of SNP rs11146020, which is located in the non-coding region of GRIN1 , Cai et al ( 2020b ) found that SNP rs3813296 located in the intron region of GRIA2 also has certain effects on the causality connections which located on the descending pathway from DLPFC to the striatum and thalamus in patients with schizophrenia. In the meantime, the interaction effects of rs11146020 and rs3813296 on causality connectivity are mainly located in the upstream pathway from the bilateral pallidum to the right caudate and the bilateral DLPFC, and negatively correlated with the Mayer–Salovey–Caruso emotional intelligence test, managing emotions score.…”
Section: Mri and Snps In Schizophreniamentioning
confidence: 99%
“…Compared with non-risk A allele carriers, patients with schizophrenia with G/G genotype of risk variant rs7914558 which is located in intron1 of the CNNM2 have smaller gray matter volumes in the bilateral inferior frontal gyri, especially the orbital region (Ohi et al, 2013 ). Among the effects of GRIA2 gene rs3813296 on white matter (Cai et al, 2020b ), the most significant effect is located on the bilateral superior corona radiata fibers. Compared with the TT genotype, patients with GT genotype have a significantly larger volume of the superior corona radiata, which leads to the dispersion of the connection strength between the left DLPFC and the right caudate (Cai et al, 2020b ).…”
Section: Mri and Snps In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations